João do Rio: língua, sociedade e identidade nacional - Craice, Luscelma Oliveira Cinachi (2013)
This paper analyzes the knowledge built around the language, society and national identity at a given time, as the product of a metalinguistic reflection, through the work of João do Rio. Chronicler par excellence of the 1900s in Brazil, João do Rio brought the literary narrative report to the Brazilian press, and by exploring the two forms of intellectual activity - literature and journalism - established himself as one of the greatest writers of his time. He transformed criticism and did reporting, and the two merged into an unpretentious, engaging, and revelatory account, a product of the ephemeral day-to-day, and without pretension to last more than one issue, since it is the product of the newspaper, but it remained in the memory and the admiration of posterity as the mundane chronicle of a rare journalist. To achieve this goal, we rely on the theoretical assumptions of the History of Linguistic Ideas, a particular attention given to the perceptible in relation to the path of the senses, in our case, the senses of a linguistic knowledge produced by the make-up of our language. Language and the linguistic instruments are historical objects that are closely linked to the formation of the country, the nation, and the State, and knowing the Portuguese language of João do Rio's time will produce knowledge about the national identity of Brazil in the late nineteenth century and early twentieth century. The act of knowing has, by definition, a temporal thickness, a horizon of retrospection (Auroux, 2001:11)